Laboratory tests for paroxysmal nocturnal hemoglobinuria. Issue 3 (March 2014) - Preis, Meir; Lowrey, Christopher H.
<x xml:space="preserve">Abstract</x> Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematological disorder that is often suspected in a patient presenting with non‐immune hemolytic anemia associated with pancytopenia or venous thrombosis. This disorder is a consequence of acquired somatic mutations in the phosphatidylinositol glycan class A (PIG‐A) gene in the hematopoietic stem cells (HSC) of patients. The presence of these mutations leads to production of blood cells with decreased glycosyl phosphatidylinositol‐anchored cell surface proteins, making red blood cells derived from the clone more sensitive to complement mediated hemolysis. The diagnosis of PNH may be difficult in some cases due a low proportion of PNH cells in the blood and occasionally due to difficulties in selecting the most appropriate diagnostic studies. The latest generation of tests allow for detection of very small populations of PNH cells, for following the natural course and response to therapy of the disease, and for helping to decide when to initiate therapy with monoclonal antibody targeting the terminal complement protein C5 (Eculizumab), anticoagulation, and in some cases allogeneic HSC transplant. In this article, we review the different diagnostic tests available to clinicians for PNH diagnosis. Am. J. Hematol. 89:339–341, 2014. © 2013 Wiley Periodicals, Inc.